Saúde mental na equipe de saúde mental do CAPS: problematizando conceitos e construindo relações - Limachi, Elysangela Koglin Ulo (2024)
This work comprises a research carried out in the Master's course in Psychology that sought to draw attention to the possible psychological suffering of professionals in the field of mental health. Its objective is to problematize the mental health of a mental health team that works in a Psychosocial Care Center located in the interior of the State of Rio Grande do Sul. In order to provide a better understanding of the topic, it began with a theoretical study that aimed to cover the implementation of public policies related to mental health in Brazil to date. In this first chapter, it was found that, even in the face of the advances provided by the Brazilian Psychiatric Reform, setbacks are possible, since changing the way of thinking of a society, or even of a small group of people, is extremely challenging. The paradigmatic changes disseminated amid the anti-asylum struggle and Psychiatric Reform still deserve reflection. In a second moment, an empirical research was undertaken that sought to observe and listen to the psychological suffering of mental health professionals. We sought professionals working in a Psychosocial Care Center (CAPS) in the interior of Rio Grande do Sul, where we reflected on professional training, the perspective of care based on Psychosocial Care, and also on the daily challenges faced in the service. It was observed that deficiencies during professional training generate a lack of preparation to act within the principles of the Psychiatric Reform, resulting in a lack of understanding of how to manage care actions within the perspective of Psychosocial Care. Concomitant to this, challenges were also observed such as: high demand in the service, isolation and lack of support within the network itself, which has generated stress, exhaustion and frustration. Mental health professionals are not exempt from psychological suffering, which has its real existence, expressing itself in both singular and complex ways. Given what was experienced in this research, it is clear that in this trajectory the mental health professional also faces his own psychological suffering, and it is at this moment that all his movement in favor of the other also turns to himself. In a context where psychosocial care and attention are prioritized, and an inclusive and broad view of people in distress, it is also important that the same principles be directed to those who provide support and a path, but who also suffer without being seen and/or heard.